2002
DOI: 10.1097/00000374-200205000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Early Responsiveness to Stimuli Paired With Different Stages Within the State of Alcohol Intoxication

Abstract: Rat pups' expression of an association between a taste signaling aversive consequences of alcohol was eliminated by the presence of a tactile stimulus that originally had signaled the absence of aversive consequences of alcohol intoxication. The results suggest the interaction of inhibitory and excitatory conditioning involving the aversive properties of alcohol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
45
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 20 publications
(49 citation statements)
references
References 56 publications
4
45
0
Order By: Relevance
“…Infant and adults usually express conditioned aversions when stimuli are paired with ethanol (Pautassi et al, 2002). The expression of conditioned tactile preferences in prior studies has required prolonged pre-exposure to the pharmacological properties of EtOH (twenty days or more; Bienkowski et al, 1995;Reid et al, 1985).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Infant and adults usually express conditioned aversions when stimuli are paired with ethanol (Pautassi et al, 2002). The expression of conditioned tactile preferences in prior studies has required prolonged pre-exposure to the pharmacological properties of EtOH (twenty days or more; Bienkowski et al, 1995;Reid et al, 1985).…”
Section: Discussionmentioning
confidence: 99%
“…In turn, phase 2 was aimed at pairing the tactile CS with the initial, early ethanol postabsorptive interval, when blood ethanol concentrations are still rising. It has been suggested that during the onset of the state of intoxication ethanol may be exerting appetitive unconditional effects, while aversive effects are likely to emerge at later stages (Risinger & Cunningham, 1992;Pautassi et al, 2002). Hence, duration of phase 2 was meant to restrict conditioning to a temporal window where appetitive effects of the drug are more likely to be encountered.…”
Section: Second Conditioning Phasementioning
confidence: 99%
“…This tub was kept at 34° C by means of a heating pad placed underneath. Following this initial isolation period subjects were implanted in their cheek with a polyethylene cannula (Pautassi et al, 2002).…”
Section: Methodsmentioning
confidence: 99%
“…On the other hand, aversive effects of the drug are easily found by pairing a novel flavor or distinctive place with the post absorptive effects of EtOH. Animals will later exhibit strong taste or place avoidance, particularly when a high dose of EtOH is employed (Broadbent et al, 2002;Fidler et al, 2004;Pautassi et al, 2002). …”
Section: Introductionmentioning
confidence: 99%
“…As with adult animals, high ethanol doses (1.2-3.0 g/kg yielding peak blood ethanol levels equivalent to 70-175 mg/100 ml, respectively) (84) act as aversive unconditioned stimuli in the infant rats, supporting the acquisition of chemosensory as well as tactile-conditioned aversions (65,(85)(86)(87)(88). Recently, it was reported that after pairing a surrogate nipple or a novel odor with low ethanol doses yielding 15-20 mg/100 ml blood ethanol levels, newborn rats (3-24 hrs old) increase their appetitive suckling activity in the presence of this nipple or odor; thus, this result indicated positive reinforcement from the ethanol (89-91).…”
Section: Learning About Ethanol In the Fetusmentioning
confidence: 99%